Hybrid perovskite films by a new variant of pulsed excimer laser deposition: a room-temperature dry process - Bansode, Umesh P.; Naphade, Rounak; Game, Onkar S.; Agarkar, Shruti A.; Ogale, Satishchandra (Journal of Physical Chemistry C, 2015)
A new variant of the classic pulsed laser deposition (PLD) process is introduced as a room-temperature dry process for the growth and stoichiometry control of hybrid perovskite films through the use of nonstoichiometric single target ablation and off-axis growth. Mixed halide hybrid perovskite films nominally represented by CH(3)NH(3)PbI(3-x)A(x) (A = Cl or F) are also grown and are shown to reveal interesting trends in the optical properties and photoresponse. Growth of good quality lead-free CH3NH3SnI3 films is also demonstrated, and the corresponding optical properties are presented. Finally, perovskite solar cells fabricated at room temperature (which makes the process adaptable to flexible substrates) are shown to yield a conversion efficiency of about 7.7%.

Hybrid perovskite quantum nanostructures synthesized by electrospray antisolvent-solvent extraction and intercalation - Naphade, Rounak; Nagane, Satyawan; Shanker, G. Shiva; Fernandes, Rohan; Kothari, Dushyant; Zhou, Yuanyuan; Padture, Nitin P.; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2016)
Perovskites based on organometal lead halides have attracted great deal of scientific attention recently in the context of solar cells and optoelectronic devices due to their unique and tunable electronic and optical properties. Herein, we show that the use of electrospray technique in conjunction with the antisolventsolvent extraction leads to novel low-dimensional quantum structures (especially 2-D nanosheets) of CH3NH3PbI3- and CH3NH3PbBr3-based layered perovskites with unusual luminescence properties. We also show that the optical bandgaps and emission characteristics of these colloidal nanomaterials can be tuned over a broad range of visible spectral region by compositional tailoring of mixed-halide (I- and Br-based) perovskites.
Keywords: 2D nanostructure systems; antisolvent-solvent extraction; bandgap tuning; electrospray; nanosheets; perovskite; quantum dots